6-6(x+3)+5x=7+6

Simple and best practice solution for 6-6(x+3)+5x=7+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-6(x+3)+5x=7+6 equation:



6-6(x+3)+5x=7+6
We move all terms to the left:
6-6(x+3)+5x-(7+6)=0
We add all the numbers together, and all the variables
-6(x+3)+5x+6-13=0
We add all the numbers together, and all the variables
5x-6(x+3)-7=0
We multiply parentheses
5x-6x-18-7=0
We add all the numbers together, and all the variables
-1x-25=0
We move all terms containing x to the left, all other terms to the right
-x=25
x=25/-1
x=-25

See similar equations:

| n/0.2=0.06/2 | | -18x-18x+47x=13-13 | | x^2+15x-694=0 | | 3w2=2w-16=0 | | -3/7x=42 | | 50=13x | | 2(a+3)=4-3(4+8) | | -11x-13=5 | | 4(x+3)-4=7x+2 | | 2x/3+3=9 | | -7(a+2)-4=24-a | | 3m(3+8)=m | | -14x-18=15 | | 6(u-3)=-7u+34 | | 9x-6=10x-10 | | 8c=$60.00 | | 8x-1=4x+1 | | 4(4x-9)=2(8x+6) | | 18=2x-7 | | n/0.4=0.08/5 | | 5/8c=145 | | -1/2(p=2)=-3-p | | 3(x-5)=5(x-4) | | 3/5r=21 | | p-3(4+4p)=-78 | | .66x=6/4 | | 3(x^2)-62x-240=0 | | 17x+19=-3 | | 4/5r=7.75 | | -4x-13=9 | | 2(4x-7)=-15 | | 2(4x-7=-15 |

Equations solver categories